The Role of Multi National Cooperation (MNC) in Developing Countries Case Study : â€œFerrero Group's Influence on Enhancement Cocoa Farms in CÃ´te d'Ivoireâ€: Pengaruh Kerjasama Multi Nasional (MNC) di Negara Berkembang Studi Kasus ''Pengaruh Grup Ferrero pada Peningkatan Perkebunan Kakao di Pantai Gading'' - Regga Fajar Hidayat; Feni Fitriani Putri Rozi; Siti Aminah Chaniago; Bagaskara Sagita Wijaya (UNIDA Gontor, 2023)
This article will discuss Ferrero Group's influence on the enhancement of agricultural cocoa in CoÌ‚te d'Ivoire. Using the objective qualitative method to know how far that influence has been awarded the Ferrero Group to the CoÌ‚te d'Ivoire country in agriculture cocoa. CoÌ‚te d'Ivoire is a developing country that can say it still lacks knowledge in agriculture even though 40% of world cocoa comes from CoÌ‚te d'Ivoire. Respond matter this is the Ferrero Group initiative to empower farmers' existing chocolate with three main pillars, namely: 1). Increase the level of life for farmers and communities 2). Protect the right of children 3). Protect natural capital. Through the Cocoa Horizons program, Ferrero Farming Values return the right child, agroforestry, and against deforestation. Through its programs, the Ferrero Group is capable of pushing agriculture CoÌ‚te d'Ivoire cocoa by providing knowledge transfer and technology transfer to optimize agriculture cocoa. Ferrero also delivers education for the public will haka children for learning and play through the Ferrero Hazelnut Company Child Labor Monitoring & Remediation System. As well as building sustainable agriculture without damage natural through agroforestry and against deforestation. Keywords: Cocoa Agroforestry, Cocoa Horizons, Deforestation, Ferrero Farming Values.